Liturgical initiatives and moratorium debates in Africa: An Afro-ecclesiological perspective - Gathogo, Julius (Stellenbosch Theological Journal, 2023)
African ecclesiology has experienced peculiar theological scenes right from the days of the Arianism and Donatism controversies in the first century to the present moment when a liturgy of Africa is still a pipedream. By use of theo-historical-analytical design, this article explores the quest for a liturgy of Africa by retracing some key trends such as the moratorium debates of the 1970s and other key attempts at the inculturation of liturgy in Africa. In other words, was the call for a moratorium by John Gatu and other African ecclesiastical leaders geared towards a liturgy of Africa rather than a liturgy for Africa? What are the concrete areas that needs “liturgical inculturation” especially in regard to the Eucharist? The article sets out on the premise that the calls for moratorium since the 1970s were part of Afro-Ecclesiastical and Afro-liturgical initiatives, a phenomenon that Africa has yearned for since the era of the 19th and 20th century missionary enterprises. In its methodology, the article has extensively reviewed existing literature in regard to the quest for a “Liturgy of Africa” as opposed to the foreign induced “Liturgy for Africa,” by illustrating from some mainline churches and the African instituted churches’ ecclesiological discourses. The article has also relied heavily on the author’s experiences as a participant observer among some African churches. Certainly, the quest for a liturgy of Africa is in its initial stage; and the task ahead is tremendous. In view of this, we should swing into action, take up the challenge with courage and creativity, till Christianity in Africa is Africanized. In post Covid-19 Africa, a more creative liturgical practicum will be the way to go.